Clinical Profile of Cirrhotic Patient with Esophageal Varices WhoUndergone Band Ligation in Cipto Mangunkusumo Hospital - Kalista, Kemal Fariz; Lesmana, Cosmas Rinaldi Adithya; Sulaiman, Andri Sanityoso; Gani, Rino Alvani; Hasan, Irsan (UI Scholars Hub, 2019)
Introduction. Liver cirrhosis (LC) is the end stage of chronic liver disease. One of the main complication caused by LC is esophageal varices (EV). Bleeding due to EV rupture is the main cause of mortality in patient with LC. EV band ligation can be used for primary or secondary prophylaxis to prevent bleeding. The purpose of this study was to know the clinical profile of LC patient with EV who underwent band ligation and who not underwent band ligation. Methods. A cross-sectional study was conducted in LC patients who underwent esophagogastroduodenoscopy (EGD) in Procedure Room Division of Hepatobiliary, Departement of Internal Medicine, Cipto Mangunkusumo Hospital from 2016 to 2017. Results. During January 2016-December 2017, a total of 313 patients underwent EGD. Most of them ( 73.2%) were male and predominantly > 60 years (34,2%). Most common LC etiology was hepatitis B (51.8%., There were 22% subjects with hepatocellular carcinoma (HCC). EV band ligations were done in 146 (46.7%) patients. In the ligation group, 56.2% patients were from outpatient clinic. The most common EGD indication (39%) was evaluation from previous ligation. Of 41.8% patients had Child-Turcotte-Pugh (CTP) class-A condition, 82.9% patients had MELD score < 15, 61.6% patients had large EV, 22.1% had red color sign (RCS) and 84,9% patients had portal hypertensive gastropathy. There were significant differences in CTP class, ascites, platelet, bilirubin, and albumin between ligation group compare to non-ligation group. Conclussion. Most of LC patients who underwent EV band ligation had CTP class-A, came from the outpatient clinic. The Jurnal Penyakit Dalam Indonesia | Vol. 6, No. 1 | Maret 2019 | 37 Profil Klinis Pasien Sirosis Hati dengan Varises Esofagus yang Menjalani Ligasi Varises Esofagus di Rumah Sakit Dr. Cipto Mangunkusumo main finding in EGD was large EV with portal hypertensive gastropathy. There were significant differences in liver functions between patient in ligation group compared to patient in non-ligation group.